PENAPISAN BAKTERI YANG BERASOSIASI DENGAN SPONS JASPIS SP. PENGHASIL ENZIM AMILASE - Dede Mahdiyah (Universitas Lambung Mangkurat, 2012)
Sponges have been known as excellent sources for natural products such asbioactive compounds. Their bioactivities include enzyme inhibitors, cell divisioninhibitors,antiviral, antifungal, antimicrobial, etc. The aims of study were to yielded ofamilase from association sponge Jaspis sp. With bacteria. The bacteria was isolated byusing sea water complete media and to determine amilase toward using soluble starch.Among 136 isolates examined, thirty three isolates yielded amilase.